LISTENING PODCASTS AND APPLICATIONS (Ustozlar uchun, 2026)
This article examines the role of listening podcasts and mobile applications in teaching and learning English as a Foreign Language (EFL). It analyzes how these digital tools influence learners’ listening comprehension, vocabulary acquisition, pronunciation, and overall language proficiency. The paper highlights the strengths and weaknesses of using podcasts and applications, showing that they provide authentic input, learner autonomy, and flexible access to diverse audio content. The study concludes that integrating podcasts and language learning applications into regular English instruction significantly enhances listening skills and learner motivation.